IgG4-related Diaphragmatic Inflammatory Pseudotumor - Yoshida, Naoki; Kikuta, Kazuhiro; Miura, Shin; Matsumoto, Ryotaro; Sano, Takanori; Hamada, Shin; Takikawa, Tetsuya; Masamune, Atsushi; Tanaka, Yu; Kume, Kiyoshi; Unno, Michiaki; Hongo, Seiji; et al. (Internal Medicine, 2021)
A 71-year-old man underwent surgery for a pancreatic neuroendocrine tumor. Follow-up imaging showed swelling of the remnant pancreas, and he was histologically diagnosed with autoimmune pancreatitis based on endoscopic ultrasonography-guided fine-needle aspiration specimens. After two years, a tumor appeared on the liver surface. Although we planned to perform laparoscopic partial hepatectomy, the intraoperative findings showed that the tumor was located in the diaphragm. Partial resection of the diaphragm was performed, and the final diagnosis was an immunoglobulin G4-related inflammatory pseudotumor in the diaphragm. To our knowledge, this is the first reported case of an immunoglobulin G4-related diaphragmatic inflammatory pseudotumor.